Implementing the Zachman Framework to Optimize Business Process Management in Gaming Applications - Ilma Wulansar Hasdiansa; Sitti Hasbiah (Indonesian Journal of Enterprise Architecture, 2024)
The gaming industry has witnessed rapid growth over the past few decades. Games are no longer perceived solely as entertainment but have evolved into a significant revenue-generating industry. One popular game, Hayday, offers an engaging experience centered on farming and business. To enhance business process management within the game, the concept of Enterprise Resource Planning (ERP) is highly relevant. This paper explores the implementation of enterprise architecture based on the Zachman Framework within the context of Hayday. The Zachman Framework serves as a structured methodology to design and manage enterprise architecture effectively. By leveraging the framework, organizations can map various perspectives into a comprehensive 6x6 matrix, enabling a deeper understanding of their enterprise architecture. This study adopts a case study approach using qualitative methods. The findings and discussion elaborate on the implementation of the Zachman Framework in the Hayday game application across six key perspectives: data, process, location, people, time, and motivation. This implementation aims to optimize business process management in the game and to lay the groundwork for the development of suitable ERP software.